Analisis Kadar Metabolit Primer Andaliman (Zanthoxylum acanthopodium DC.) dan Pengaruhnya terhadap Sifat Kimia Tanah - Evi Winda Sari Sianipar; Nur Asyiah Dalimunthe; Rizal Aziz; Angga Ade Sahfitra; Raudha Anggraini Tarigan (Universitas Medan Area, 2026)
Plant biomass can be used as an organic material to improve soil chemical properties by supplying carbon and nutrients released during decomposition. This study aimed to analyze the primary metabolite composition of andaliman (Zanthoxylum acanthopodium DC.) biomass and evaluate its effects on soil chemical properties. A completely randomized design was used with five andaliman biomass levels, namely P0 (0%), P1 (2.5%), P2 (5%), P3 (7.5%), and P4 (10%) based on soil weight, with three replications. Moisture, ash, protein, fat, and carbohydrate contents were determined using AOAC proximate methods, while soil pH, organic C, total N, available P, exchangeable K, and cation exchange capacity were analyzed after incubation. Data were subjected to ANOVA followed by DMRT at the 5% level. Andaliman biomass contained 71.93% moisture, 13.56% carbohydrate, 7.67% protein, 3.95% ash, and 3.89% fat. Its application significantly affected all observed soil chemical properties. The P4 treatment produced the best results, with soil pH of 6.36, organic C of 3.47%, total N of 0.35%, available P of 28.94 mg kg⁻¹, exchangeable K of 0.63 cmol(+) kg⁻¹, and CEC of 30.68 cmol(+) kg⁻¹. Andaliman biomass therefore has potential as a local organic ameliorant for sustainable soil management.